Surgical wound infections – a historical review - Newsom, Bill (International Journal of Infection Control, 2008)
Until the 1860’s surgical site infection was so severe that surgeons rarely operated. Erichsen, from University College Hospital in London coined the phrase ‘ hospitalism’ for what we now call healthcare-associated infection’. He provided 13 recommendations for its prevention - many of which remain valid to-day. However it was his pupil Joseph Lister who first made surgery possible using his ‘antiseptic method’ based on a phenolimpregnated wound dressing. This was later developed into the ‘aseptic surgery’ of to-day.